2013
DOI: 10.1366/13-07001
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Hybrid Morphology Nanoarrays as Plasmonic Raman Probes for Antimicrobial Detection

Abstract: Advances in nanofabrication have allowed the production of new and more reproducible substrates for the Raman detection of trace antimicrobials in water. The superior substrate uniformity combined with the ability to control surface morphology represents a significant step forward in the design of substrates with improved enhancement factors and trace-detection capabilities. The work presented herein successfully combines electron-beam lithography (EBL) and reactive ion-etching (RIE) protocols for the construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The standard operating procedure for signal normalization and EF calculation, particularly the number of molecules present in the sample volume ( N vol ), is readily available in the literature. 60 Similarly, the numerical density of molecules present at the surface ( N surf ) was determined by calculating the total surface area, for instance an ellipsoid, for the elliptical patterns (acacia leaf, sunflower, acacia pinnate, orchid and Asian Lilium ). The top area was empirically calculated using the average length and width of a particle based on using the SEM images (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard operating procedure for signal normalization and EF calculation, particularly the number of molecules present in the sample volume ( N vol ), is readily available in the literature. 60 Similarly, the numerical density of molecules present at the surface ( N surf ) was determined by calculating the total surface area, for instance an ellipsoid, for the elliptical patterns (acacia leaf, sunflower, acacia pinnate, orchid and Asian Lilium ). The top area was empirically calculated using the average length and width of a particle based on using the SEM images (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…9,59 For instance, the first generation of arrays are elliptical prisms, 150 nm long to 50 nm wide, in a ratio in which the longest axis aligned with the polarization vector of laser source produces the most intense radiation scattering. 28,60 Likewise, larger particle sizes and densities have been explored; 60 and although proven to be SERS active, their enhancement is yet far from that suggested for denser arrays with potential inter-particle coupling. 28,61 Finally, ZEP-520A (Zeon Chemicals L.P.) was selected as the standard EBL photoresist since it was currently validated at the EBL facility to enable reproducible nanofabrication at the 50 nm threshold of the LSP responses.…”
Section: Introductionmentioning
confidence: 99%
“…To be integrated into lab-on-a-chip [47] or other portable T-LSPR devices [21], including SERS chips [48,49], the LSPR thin films might be combined with microfluidic chips [50][51][52], significantly reducing the consumption of analytes, among other advantages [44,46,53]. The microfluidic LSPR chip might be composed of two main components, where the plasmonic thin film, e.g., deposited on glass, is chemically bonded to a microfluidic module, usually a polymer like poly(dimethylsiloxane) (PDMS), using plasma treatment to functionalize its surface [21,50,54].…”
Section: Introductionmentioning
confidence: 99%
“…Significant strives have been made on substrate development since it has been observed that adjustments in simple geometrical parameters (i.e., interparticle space, gap and morphology) can tune plasmonic responses to specific excitation frequencies thus optimizing substrate performance and reproducibility. 613…”
Section: Introductionmentioning
confidence: 99%